Branding proposal for Blossomz : a case study of brand building and brand management - Pan, Jing (2008)
This paper is a branding proposal for a local apparel retailer, Blossomz. It begins with the theoretical framework of branding concepts and methodologies and then goes into research done on Blossomz’s potential customers, competitors and the company itself. Based on the research done, we identify the internal and external issues that Blossomz is facing and these are what our branding proposal aims to solve.